2007
DOI: 10.1007/s00221-007-1233-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pathologic and simulated visual dysfunctions on the postural system

Abstract: Visual control has an influence on postural stability. Whilst vestibular, somatosensoric and cerebellar changes have already been frequency analytically parameterized with posturography, sufficient data regarding the visual system are still missing. The aim of this study was to evaluate the influence of pathologic and simulated visual dysfunctions on the postural system by calculating the frequency analytic representation of the visual system throughout the frequency range F1 (0.03-0.1 Hz) of Fourier analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 51 publications
7
85
0
7
Order By: Relevance
“…The ANOVA showed a significant effect of condition (F (3,24) =17.99, p<0.0001 and F (3,24) =23.51, p< 0.0001, respectively, for the deviation measured at far and at near distance), but the least significant difference post hoc test showed only a significant difference between the pre and the other conditions. Note that the deviation measured after prism wearing was not significant different with respect to the two post surgery conditions.…”
Section: Deviation Changes In the Different Conditions Testedmentioning
confidence: 80%
See 1 more Smart Citation
“…The ANOVA showed a significant effect of condition (F (3,24) =17.99, p<0.0001 and F (3,24) =23.51, p< 0.0001, respectively, for the deviation measured at far and at near distance), but the least significant difference post hoc test showed only a significant difference between the pre and the other conditions. Note that the deviation measured after prism wearing was not significant different with respect to the two post surgery conditions.…”
Section: Deviation Changes In the Different Conditions Testedmentioning
confidence: 80%
“…Recently, Friedrich's research group [3] examined postural control in normal adults and adults with visual disabilities. They showed that, when visual inputs are deficient, compensation mechanisms such as vestibular and somatosensory inputs and cerebellar processes can be activated to ensure good postural control.…”
Section: Introductionmentioning
confidence: 99%
“…The instability of the test subject is greater when the quotient is higher. This value correlates strongly with the values "area of sway", "length of sway" or "amount of sway" of other investigational systems, such as Amplaid S.VeP (Amplaid, Milan, Italy) and the Balance Master and Equitest (Neurocom, Clackamas, USA) [11]. -Weight distribution, expressed as the "weight distribution index" (WDI) and calculated by recording the weight at each of the four sensors on the pressure plate.…”
Section: Methodsmentioning
confidence: 97%
“…The body sway described with the use of the curve of the stabilogram and statokinesiogram (in the test with the eyes closed) reached clearly higher values in cases of individuals who were not engaged in regular sport activity. Studies comparing static and dynamic balance among both blind and healthy participants show that up to 70% of the information needed to assess balance comes from the sense of sight [7,28]. The more complex the task to accomplish is, the greater the dependence on sight [34].…”
Section: Discussionmentioning
confidence: 99%